2003
DOI: 10.1046/j.1460-9568.2003.02698.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtype switching of vesicular glutamate transporters at parallel fibre–Purkinje cell synapses in developing mouse cerebellum

Abstract: Two subtypes of the vesicular glutamate transporter are expressed differentially in two excitatory afferents synapsing on to Purkinje cells: VGluT1 (BNPI) in axon terminals of cerebellar granule cells (i.e. parallel fibres; PFs) and VGluT2 (DNPI) in those of the inferior olivary neurons (climbing fibres; CFs). In the present study, we examined their expression in the developing mouse cerebellum. By in situ hybridization, the inferior olivary nucleus selectively expressed VGluT2 mRNA through postnatal life. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
261
2
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(292 citation statements)
references
References 38 publications
24
261
2
3
Order By: Relevance
“…The testican gene turned out to be expressed mainly in stellate cells of the cerebellum. We selected 14 genes from the previous study and three additional TTXsuppressive genes which were identified in this study and expressed in the mature cerebellum (10)(11)(12). PCR analysis confirmed that the expression of all 17 genes was inhibited by TTX to different degrees, ranging from 15-85% ( Fig.…”
Section: Resultsmentioning
confidence: 61%
“…The testican gene turned out to be expressed mainly in stellate cells of the cerebellum. We selected 14 genes from the previous study and three additional TTXsuppressive genes which were identified in this study and expressed in the mature cerebellum (10)(11)(12). PCR analysis confirmed that the expression of all 17 genes was inhibited by TTX to different degrees, ranging from 15-85% ( Fig.…”
Section: Resultsmentioning
confidence: 61%
“…The VGLUT1 KO mice die at the age when a strong upregulation of VGLUT1 through newly emerging VGLUT1 synapses as well as a replacement of the previously predominant VGLUT2 isoform in cerebellar, hippocampal, and cortical neurons occur (19,26). This down-regulation of VGLUT2 is independent of VGLUT1 up-regulation and biological activity, given that it occurs in VGLUT1 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these brain regions exclusively express one isoform, and although the majority of glutamatergic neurons express either VGLUT1 or VGLUT2, several studies describe coexpression of both isoforms, for example, in cerebellar mossy fiber terminals (16,17) and cerebellar unipolar brush cells (18). Most remarkably, a developmental switch from VGLUT2 to VGLUT1 occurs in the hippocampus, cortex, and cerebellum (19). The third isoform, VGLUT3, is less widely expressed than the other two.…”
mentioning
confidence: 99%
“…In contrast, doublecortin, Homer2, MARCKS-like protein, caspase-3, and VGluT2 genes, which are all FK-down genes, have been reported to be significantly expressed in the EGL during the postnatal period (26)(27)(28)(29)(30). We performed in situ hybridization of cerebellar sections at P8 and The numbers and proportions of the Depo-down genes and Depo-up genes (a total of 87 genes) (C) and those of the FK-up genes and FK-down genes (a total of 77 genes) (D) are indicated in each group of the Dev-up genes, Dev-down genes, and non-Dev genes.…”
Section: Expression Of Fk506-responsive Genes In Premigratory and Posmentioning
confidence: 97%